Determinants of community-based health insurance membership renewal decision among rural households in Kellem Wollega zone, Oromia regional state, Ethiopia: a community-based cross-sectional study - Geta, Edosa Tesfaye; Lushe, Kifile Abdisa; Desisa, Adisu Ewunetu; Terefa, Dufera Rikitu; Cheme, Melese Chego; Shama, Adisu Tafari; Lema, Matiyos (Frontiers in Public Health, 2024)
Background Despite the fact that community-based health insurance (CBHI) is a promising program to achieve the goal of universal health coverage (UHC), it faces challenges that are not only due to low enrollment but also due to membership renewal decision that impact its sustainability. Hence, the study aimed to identify the determinants of CBHI membership renewal decision among rural households in Kellem Wollega zone, Ethiopia. Methods The study was conducted in Kellem Wollega, Ethiopia, among rural households from March 30–April 30, 2022, using a community-based cross-sectional study design. An interviewer-administered structured questionnaire through face-to-face interviews was used. Using a systematic random sampling method, 551 households were selected making 540 (98%) response rates. The data was entered into EPI Data 3.1 and analyzed using SPSS 25 software. Descriptive statistics, binary, and multiple logistic regressions were performed. Using multiple logistic regressions, a significant association between the CBHI membership renewal decision and independent variables was identified, declaring the statistical significance level using a 95% confidence interval (CI) at p < 0.05. Results The overall rate of CBHI membership renewal decision among households was estimated to be 365 (67.6%, 95% CI = 63.7–71.5%). The factors that significantly influenced the households’ membership renewal decision were family size (AOR = 0.46, 95% CI = 0.25–0.86), low literacy status (AOR = 0.28 95% CI = 0.12–0.64), lower than middle-level of wealth index (AOR = 9.80, 95% CI = 2.75–34.92), premium affordability (AOR = 4.34, 95% CI = 2.08–9.04), unavailability of services (AOR = 0.26, 95% CI = 0.12–0.55), trusting in health facilities (AOR = 5.81, 95% CI = 2.82–11.94), favorable providers’ attitude toward members (AOR = 8.23, 95% CI = 3.96–19.64), good quality of service (AOR = 4.47, 95% CI = 2.28–8.85) and health care seeking behavior (AOR =3.25, 95% CI = 1.32–7.98). Conclusion The overall CBHI membership dropout decision rate among rural households was high, which could affect health service provision and utilization. Therefore, the insurance scheme and contracted health facilities should consider and work on family size and wealth status when membership premiums are calculated, the education level of households when creating awareness about the scheme, building trust in the contracted health facilities by providing all promised benefit packages of health services with good quality, and improving the attitude of health care providers towards the scheme members.